Association of Adiponectin Gene Variations with Risk of Incident Myocardial Infarction and Ischemic Stroke: A Nested Case-Control Study - Hegener, Hillary H; Lee, I-Min; Cook, Nancy R; Ridker, Paul M; Zee, Robert Y.L (Clinical chemistry (Baltimore, Md.), 2006)
Background: Adiponectin (ADIPOQ) gene variations are associated with risk of cardiovascular disease in patients with diabetes. No prospective data are available, however, on the risk of atherothrombotic disorders in persons with ADIPOQ variations who do not have diabetes. Methods: From a group of DNA samples collected at baseline in a prospective cohort of 14 916 initially healthy American men, we assessed the presence of 5 ADIPOQ genetic variants (rs266729, rs182052, rs822396, rs2241766, and rs1501299) in samples from 600 Caucasian men who subsequently suffered an atherothrombotic event (incident myocardial infarction or ischemic stroke) and from 600 age- and smoking-matched Caucasian men who remained free of reported vascular disease during follow-up (controls). Results: Genotype distributions for the variations tested were in Hardy-Weinberg equilibrium. Marker-by-marker conditional logistic regression analysis, adjusted for potential risk factors, showed an association of rs266729 [recessive: odds ratio (OR), 0.26; 95% confidence interval (CI), 0.10–0.64; P = 0.004] and rs182052 (recessive: OR, 0.40; 95% CI, 0.21–0.76; P = 0.006) with decreased risk of ischemic stroke. These findings remained significant after Bonferroni correction. Haplotype-based (constituted by rs266729, rs182052, and rs822396) conditional logistic regression analysis, adjusted for the same potential risk factors, showed an association of haplotype G-A-G (OR, 0.28; 95% CI, 0.09–0.87; P = 0.03) with decreased risk of ischemic stroke. Prespecified analysis limited to participants without baseline diabetes showed similar significant findings. Conclusions: The present prospective investigation provides further evidence for a protective role of adiponectin gene variation in the risk of ischemic stroke that was independent of the presence of diabetes.